Analisis Kepatuhan Jaga Jarak Fisik untuk Mencegah Penyebaran Covid-19 di Indonesia: Scoping Review - M. Karomah Nastiti Melania; Inge Dhamanti (Universitas Airlangga, 2023)
Background: Obedience is a positive attitude shown by someone in response to a regulation. Physical distancing is one of the ways to limit physical contact to stop the spread of infectious diseases such as Covid-19. Keeping a distance from other people when in a crowd is important to apply. Because wearing a mask is not enough to prevent someone from being exposed to other people's droplets. Physical distancing can also prevent the transmission of Covid-19 from people who are not aware that they have been infected and are not self-isolating. Objectives: This study aim to determine physical distancing obedience in a group of people who live throughout Indonesia. Methods: This study was scoping review research. Article searches were conducted through Google Scholar anf Portal Garuda.. The keywords used to search for articles included